COMPARISON OF THE EFFECT.OF ADDING.DIFFERENT.LEVELS OF DIGESTAROM AND PROBIOTICS TO THE DIET ON CARCASS CUT AND ANATOMICAL CHARACTERISTICS OF THE DIGESTIVE SYSTEM OF BROILER CHICKENS ROSS (308) - Liza Ali Fairooz and Mohammed Jard Kadhim, (Chelonian Research Foundation, 2023)
This experiment was conducted in a private field in Karbala Governorate for a period of 5 weeks from 10/1/2022 to 11/4/2022, with the aim of comparing the effect of adding different levels of Digestarom and Probiotic in the diet of broilers (Ross 308) on some aspects and anatomy of the digestive system. The research used 450 one-day-old broiler chicks, which were reared for five weeks. They were randomly distributed among six treatments, 75 chicks for each treatment, and the chicks from one treatment were distributed into three equal replicates, 25 chicks for each replicate. The control treatment was administered after the first treatment (T1) of chickens, which were fed a simple feed devoid of any additives. The second treatment (T2) chicks were fed a standard diet to which Digestarom powder was added at a weight of 2.5 gm/kg/feed. The chicks in the third treatment (T3) were given a basic diet plus probiotic powder (2.5 gm/kg/feed); the chicks in the fourth treatment (T4) were given a basic diet plus Digestarom powder (5 gm/kg/feed); and the chicks in the fifth treatment (T5) were given a basic diet plus probiotic powder (5 gm/kg/feed), and the sixth treatment (T6) hens were fed a basic meal supplemented with (2.5 gm/kg/feed) of Digestarom powder and (2.5 gm/kg/feed) of probiotic powder. The duodenum, jejunum, and ileum which are representative of the small intestine were used to compute the villus height and villus breadth during the experimental period. The results showed that adding a mixture of Digestarom powder at a rate of (2.5 gm/kg/feed) + probiotic powder at a rate of (2.5 gm/kg/feed), represented by the sixth treatment (T6), led to a significant improvement in the level of (P ≤ 0.05) histological sectioning of the intestine. Average weight of the main carcass cuts (chest and thigh) and the secondary ones (wings, neck and back), with significant differences between the treatments with regard to the carcass cuts for the treatments (T5 and T6), which recorded the highest value, followed by the fourth treatment (T4) in (weight of the chest, weight of the neck and back) and recorded the lowest. Weight increase in the weight of carcass pieces in treatment (T2). Microvilli (villus height and villus width). The results obtained compared to the control treatment (T1) were a significant.improvement.at the. level of (P ≤ 0.05) with respect to the histological segmentation of the intestine (duodenum, jejunum, and ileum). There was a. significant. improvement at. the. level of (P ≤ 0.05) in the height and width of the villi in favor of The sixth treatment (T6), while the two treatments (T2 and T3) recorded the least significant differences from the previous ones, while the lowest height and width of the villi was in the control treatment (T1).